The Relationship Between Attentional Bias, Anxiety Sensitivity, and Depression and Anxiety Symptoms: Evidence From the COVID-19 Pandemic in China - Li, Shiyi; Li, Xiao (Frontiers in Public Health, 2022)
Background: As a sudden public health event, COVID-19 pandemic in China led to a huge threat to mental health, especially causing anxiety and depression. Some studies indicated that attention bias is closely relevant to anxiety and depression. Anxiety sensitivity is a key cognitive factor in the generation and maintenance of anxiety and depression, individuals with high anxiety sensitivity tended to experience various negative emotions. The present study focuses on the role of anxiety sensitivity during the pandemic between attention bias and both anxiety and depression symptoms, especially physical and cognitive concerns. Method: 460 non-clinical participants from China conducted an online questionnaire survey between February and March, 2020. Using Attention to Positive and Negative Information Scale, Anxiety Sensitivity Index-3, and Depression Anxiety Stress-21 Scale. The data were analyzed for descriptive statistical analysis, Pearson correlations and regression analysis. The study also tested the mediating effect. Results: The results indicated that negative attention bias was significantly positively correlated with physical and cognitive concerns, physical and cognitive concerns were significantly positively correlated with depression and anxiety, and negative attention bias was significantly positively correlated with depression and anxiety(all ps<0.001). Physical and cognitive anxiety sensitivity mediated relations between negative attention bias and both anxiety and depression symptoms, and the bootstrapped 95% confidence interval did not contain 0, indicating that there is a significant mediating effect. Conclusion: Negative bias was associated with levels of anxiety and depression, and physical and cognitive anxiety sensitivity mediated associations between negative bias and anxiety and depression symptoms. The study provides theoretical support for intervention and guidance on individual mental health during the epidemic, and helps individuals increase their concern to negative emotions.